Lena Dominelli (United Kingdom), President 1996 - 2004 - Marilyn Callahan (Social Work and Society, 2008)
Professor Lena Dominelli is one of those people whose passion for social justice has made a significant difference to the lives of many people and to her profession, social work. If you have ever spent time with her, as I have done, you will know that she simply never stops. She has ideas for what must be done immediately to address current injustices and also proposes strategies for the long term. She takes action on the basis of her ideas, bringing in whoever might be able to help at a given moment on a particular issue. She draws you in with her unwavering optimism and her practical solutions and before long you find yourself in the midst of accomplishing what appeared to be impossible. A social worker par excellence.